Analisis Akses Pembiayaan dan Penerapan Murabahah pada Baitul Maal Wat Tanwil (BMT) Amanah Ummah Gumpang - Nur Hanifa, Luthfia; Mufti Arief Arfiansyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted with the aim of understanding the aspects and implementation of Murabahah financing in Baitul Maal wa Tamwil Amnah Ummah (BMT AUM) Gumpang. Murabahah is a form of buying and selling goods, where the seller determines the purchase price to the buyer, and the buyer pays by adding a profit margin. The function of BMT involves developing productive businesses and investment to improve the quality of economic activities for small and medium entrepreneurs. This includes support for savings activities as well as providing financing for economic activities. This research uses qualitative methods with a descriptive approach, and combines primary and secondary data. Secondary data was obtained from BMT AUM document archives related to research focus, access and application of Murabahah. The research results show that the implementation of the Murabahah system in BMT AUM reduces the risk of loss among the parties involved. The decision to use Murabahah as a form of financing is considered by taking into account the customer profile, whose operational targets focus on the Small and Medium Enterprises sector. One of the financing that is often carried out at BMT is the Murabahah contract, where the Murabahah contract is a sale and purchase contract where BMT acts as the seller while the customer is the buyer. This research will discuss the Murabahah contract at BMT, the concept of BMT and the Murabahah financing at BMT.